'Holistic' synaptogenesis. (22nd March 2010) - Poulopoulos, Alexandros
Abstract : Synapses between nerve cells in the mammalian brain are not only extremely numerous but also very diverse with respect to their structural and functional characteristics. This heterogeneity arises despite the fact that a set of common basic protein 'building blocks' is shared by many synapses. Among these, postsynaptic scaffolding proteins play a key role. They have the ability to assemble into membrane-tethered lattices and to adopt unique conformational states in different postsynaptic microenvironments, which may represent a key prerequisite of synapse heterogeneity. Analyses of such synaptic superstructures, rather than individual proteins and their interactions, are required to develop a mechanistic understanding of postsynaptic differentiation, synapse diversity, and dynamics.